Managing Digital Media-Based Indonesian Language Learning to Enhance Literacy: A Comparative Case Study of Adaptive Practices in Resource-Variable School Contexts - Iis Winaningsih; Ayi Najmul Hidayat (Journal of Innovation and Research in Primary Education, 2026)
Despite the integration of digital technologies in education, Indonesian students' literacy remains concerning, with PISA 2022 showing only 25% achieving basic reading proficiency. This study investigates how digital media-based Indonesian language learning is managed through classical management functions to support literacy development. A qualitative multiple case study design was employed at two public senior high schools in different regional contexts. Data were collected through semi-structured interviews with four teachers and twenty-four students, classroom observations across sixteen sessions, and document analysis. Thematic analysis was conducted using Terry's management framework encompassing planning, organizing, actuating, and controlling functions. Both schools implemented all four management functions but with different emphases. SMAN 1 Tegalwaru demonstrated high adaptive capacity through flexible planning and contingency strategies despite infrastructural limitations, while SMAN 1 Cikatomas exhibited more systematic procedural consistency. Critical gaps were identified in organizational documentation and supervision follow-up mechanisms across both sites. Unexpectedly, resource constraints at Tegalwaru stimulated independent digital literacy behaviors among students. Effective digital literacy development depends not merely on technological access but on the quality, adaptability, and systematization of learning management practices. Strengthening teachers' adaptive expertise, formalizing documentation processes, and establishing structured supervision feedback loops are essential for sustainable improvement.